2019
DOI: 10.3390/d11050071
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Condition Indices as Predictors of Lipid Content in Slimy Sculpin (Cottus cognatus)

Abstract: Slimy sculpin (Cottus cognatus) are increasingly being used as indicator species. This has primarily entailed measuring their condition, the assumption being that condition can be used as a surrogate for lipid content. While there is evidence to suggest this assumption is applicable to some fish, it has yet to be validated for C. cognatus. Further, there are several means by which one may calculate condition, the most commonly employed of which are indirect measurements of lipid content (namely, Fulton's K, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…We chose these three metrics because together they provide both a general and a specific insight into energy reserves. Body condition indices are commonly used in fisheries to quantify the fatness of a fish for a given SL (Hards et al., 2019) and adjust for the cubic effect of SL on body weight that is observed in fish. Here, we describe body condition as the residuals from the relationship between ln(WW) ~ln(SL) as per Abujanra et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose these three metrics because together they provide both a general and a specific insight into energy reserves. Body condition indices are commonly used in fisheries to quantify the fatness of a fish for a given SL (Hards et al., 2019) and adjust for the cubic effect of SL on body weight that is observed in fish. Here, we describe body condition as the residuals from the relationship between ln(WW) ~ln(SL) as per Abujanra et al.…”
Section: Methodsmentioning
confidence: 99%
“…Body condition indices are commonly used in fisheries to quantify the fatness of a fish for a given SL (Hards et al, 2019) and adjust for the cubic effect of SL on body weight that is observed in fish.…”
Section: Fish Sampling and Energetic Metricsmentioning
confidence: 99%
“…However, values of K did not show significant difference between fish from Dimon Lake and Degano Creek, indicating a robustness and good state of nutrition of both populations [36]. In this case, the use of Fulton's condition factor did not allow us to predict the lipid accumulation, as also previously suggested [37].…”
Section: Discussionmentioning
confidence: 65%
“…We examined HSI and CF for four main reasons. First, both variables are widely used indicators of the general condition of fish, with HSI generally indicating the availability of shorterterm energy reserves (i.e., liver glycogen), protein, and lipid, and CF generally associated with muscle, protein and mesenteric fat (Boujard & Leatherland, 1992;Zamal & Ollevier, 1995;De Pedro et al, 2003;Hards et al, 2019). Second, in a recent experiment on cultured Delta Smelt, HSI was the most sensitive to fasting of the many biomarkers examined, becoming significantly depressed after four days without food at 15.9 °C, and CF was also relatively sensitive to food limitation, becoming significantly depressed after 7 days of fasting .…”
Section: Methodsmentioning
confidence: 99%